2015
DOI: 10.1097/hjh.0000000000000653
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive drug use and risk of cognitive decline in the very old

Abstract: Findings provide support for an association between CCB use and a lower rate of cognitive decline in very old adults with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 35 publications
(72 reference statements)
0
28
2
5
Order By: Relevance
“…The cohort studies that aimed to assess the effect of AHMs on cognition among cognitively normal patients found a decreased risk of cognitive impairment with calcium channel blockers (CCBs), β‐blockers, angiotensin‐converting enzyme inhibitors (ACE‐Is), and diuretics (Gao et al, ; Gelber et al, ; R. Peters, Collerton, et al, ; Yasar, Zhou, Varadhan, & Carlson, ; Table ). Demir, Gürol, Özyiğit, and Üresin () performed a cross‐sectional study and did not find a difference in the Mini Mental State Examination scores between renin angiotensin system (RAS) blocker users (angiotensin 1 receptors blockers [ARBs] and ACE‐Is) and other AHM users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cohort studies that aimed to assess the effect of AHMs on cognition among cognitively normal patients found a decreased risk of cognitive impairment with calcium channel blockers (CCBs), β‐blockers, angiotensin‐converting enzyme inhibitors (ACE‐Is), and diuretics (Gao et al, ; Gelber et al, ; R. Peters, Collerton, et al, ; Yasar, Zhou, Varadhan, & Carlson, ; Table ). Demir, Gürol, Özyiğit, and Üresin () performed a cross‐sectional study and did not find a difference in the Mini Mental State Examination scores between renin angiotensin system (RAS) blocker users (angiotensin 1 receptors blockers [ARBs] and ACE‐Is) and other AHM users.…”
Section: Resultsmentioning
confidence: 99%
“…The cohort studies that aimed to assess the effect of AHMs on cognition among cognitively normal patients found a decreased risk of cognitive impairment with calcium channel blockers (CCBs), β-blockers, angiotensin-converting enzyme inhibitors (ACE-Is), and diuretics (Gao et al, 2013;Gelber et al, 2013;R. Peters, Collerton, et al, 2015;Yasar, Zhou, Varadhan, & Carlson, 2008; Table 1).…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%
“…Another oldest old study, the Newcastle 85 plus, showed that having high BP defined as SBP/DBP ≥130/85 mm Hg or treatment was associated with better global cognitive function over 5 years . The Vantaa 85 plus study also reported the same result, where lower SBP increased mortality among people aged 85 or more with no significant relationship between baseline BP and dementia occurrence …”
Section: Target Bp In the Oldest Oldmentioning
confidence: 90%
“…Проведен анализ литера-туры (15 наблюдательных исследований и РКИ) за последние 5 лет. В 6 исследованиях были представлены результаты лечения АК [17,18,[42][43][44][45], в 5 из них показана польза использования АК -снижался риск развития когнитивных нарушений или деменции [17,18,42,43,45], в 2 исследованиях результаты достигли статистической значимости -Newcastle 85+ [42] и Veteran's Affairs medical database США [17]. В исследовании Newcastle 85+ приняли участие 238 пациентов в возрасте ≥85 лет с АГ, получающих АГТ.…”
Section: мета-анализыunclassified
“…В 8 исследованиях изучали применение диуретиков, в 7 из них выявлена польза диуретиков в плане снижения риска развития когнитивных нарушений или деменции [17,18,[42][43][44][45][46], в трех результаты достиг ли статистической значимости: GEMS [18], Cache County [43], Veteran's Affairs medical database, США [17]. Среди последних, в исследованиях GEMS [18] и Cache County [43] показано, что терапия диуретиками статистически значимо снижает риск развития БА [18,43], а в исследовании Veteran's Affairs medical database, США [17] на фоне приема диуретиков обнаружено статистически значимое снижение риска развития деменции [17].…”
Section: мета-анализыunclassified